The Influence of Product Difference, Price Determination, and Brand Image on the Purchase Decision of KFC Fast Food (Kentucky Fried Chicken) in Surabaya City - Desy Windi Prawita; Wilma Cordelia Izaak; Supriyono (PT FORMOSA CENDEKIA GLOBAL, 2023)
Lifestyle changes can occur as a result of people becoming more pragmatic and instant in their thinking as a result of technological advances. The purpose of this study is to dissect the ways in which consumers in Surabaya City, Indonesia make judgments about whether or not to buy fast food from KFC (Kentucky Fried Chicken). Customers who have purchased and eaten at KFC restaurants in Surabaya City are included in the sample population. Purposive sampling was used, resulting in a total of 108 responses. A questionnaire or Likert scale was distributed as a tool to collect data. Quantitative methods and primary and secondary sources of information are used in this kind of study. PLS was the method used to analyze the data. Purchasing decisions were found to be positively and significantly influenced by factors including product differentiation, pricing, and brand image.